Bioactive compounds present in olive oil and its by-products: bibliographic review (Research, Society and Development, 2022)
The objective of the study was to investigate what is being questioned by renowned researchers from all over the world, that is, to speculate on the countries that publish the most when it comes to olive oil and its derivatives, which are the largest producers, what is the quality of these products offered to the market, which are the best techniques to preserve the compounds beneficial to health, in addition to gaps that can instigate new elucidative research. It was carried out through a literature review, using the descriptors ¨Olive oil¨ and ¨Bioactives¨. The search was refined aiming only at articles as the form of the document, with publication in the years 2021 and 2022. Subsequently, the selected articles were directed to bibliometric analysis. With the 109 pre-selected articles in hand, a new refinement was carried out, analyzing 78 articles, which were categorized into five topics of most significant importance: Residues from olive oil production, the technological process of olive oil analysis, chemical parameters of different cultivars, bioactive compounds, the process of determining bioactive compounds. After a thorough analysis of all selected articles, initially referring to bioactive compounds and olive oil, and during the addition of by-products of olive oil production, one can prove the benefits of bioactive compounds, ways to better preserve them, adding to some trends of sustainability and preservation of the environment and, finally, identification of methods that can become promising: bioinformatics to predict medicinal properties and sensorial analysis corroborating with analytical and chemical techniques.